Integrated nutrient management in calendula (Calendula officinalis L.) grown in partially reclaimed sodic soil condition - L Bahadur, S K Tewari, D Singh, R C Nainwal, (Journal of Spices and Aromatic Crops, 2015)
To study the effect of nutrient management on growth and flower yield of Calendula, field experiments were carried out during 2009 and 2010. Results indicated that significantly higher plant height (40.6 cm), number of leaves (142) at 90 days, total number of flowers plant-1 (126), total fresh weight of flowers (87.5 q ha-1) and dry weight of flowers (25.0 q ha-1) were observed by the application of 10 t farmyard manure (FYM) + ½ NPK + spraying of micronutrients followed by sole application of recommended dose of inorganic fertilizer (i.e. NPK@ 80:30:30 kg ha-1) which was at par with application of half dose of recommended dose of inorganic fertilizer supplemented with half dose of organic fertilizer. Application of 20 t FYM ha-1 improved the soil physicochemical parameters i.e. pH, EC, organic carbon and available NPK in comparison to control.